Syariat dan Perundang-undangan; Proses Kebijakan dan Konten Peraturan Daerah Keagamaan di Bulukumba - Amril Maryolo AR (Mazahibuna: Jurnal Perbandingan Mazhab, 2019)
In this section it aims to describe the context of regional policy in the frame of sharia-compliant regional regulations in Bulukumba regency. Explain the legal basis, the political process of public policy, and the content of religious regulations as a reference in analyzing the phenomena behind the implementation of religious regulations in Bulukumba. By linking this matter, it is expected to be able to see the role of the actors and institutions involved in implementing the religious regulation, whether it is in line with what is aspired to form a religious community according to the vision of the Bulukumba government or vice versa.Keywords: Religious Regulation, Policy Process, Local Regulation Content